Elementos delimitadores del derecho a vacaciones - Gorelli Hernández, Juan (2014)
Among the different rights that workers are entitled to, the right to vacations has currently become one of the most relevant. However, many questions could be made regarding thesaid  entitlement:  What do we mean when we refer to vacations? Which are its mainelements? What is its purpose?In the present article, the author answers those questions in the light of several doctrinal studies, international legislation and constitutional jurisprudence. He also stresses the role the International Labor Organization Convention 132 plays on the matter, as well as the importance of the respect of freedom of association.